BUILDING CHARACTER EDUCATION IN RUMI CHILDREN IN SUMUR BATU VILLAGE, BANTAR GEBANG - BEKASI CITY - Leroy Holman Siahaan; Darmeinis (International Conferences on Early Childhood Education Proceedings, 2024)
Character education in early childhood is an effort to instill commendable behavior in children, including behavior in worship, behavior as a good citizen, behavior in interacting with other people and the environment, and commendable behavior that is beneficial for their life success. Character education is carried out in every environment where children are. The family environment is the first environment that children encounter. Parents have the responsibility to instill good attitudes in their children. Parents should not hand over their children's character education to teachers. Parents and teachers are models that children will imitate and emulate, both in their words and actions. Instilling character in children can be done through advice, habituation, example and strengthening